The impact of brand switching antecedents on consideration set construction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Marketing at Massey University - Lees, Gavin (Massey University, 2004)
Understanding brand switching is important to marketers because a brand switch has the potential to impact on an organisation's share of a customer's wallet. Therefore, the objective of this research was to determine what the impacts, of the antecedents to a brand switch, will be on the construction of a purchase repertoire and consideration set in a subscription market. This study, into the new area of post-switch consideration set construction, and the position of the previous main brand, shows that the construction of a consumer's consideration set is dependent on the reasons for the brand switch. Whilst consumers switch brands for a multitude of reasons, the literature shows these reasons can effectively be grouped together into three categories: stochastic reasons, expectation disconfirmation, and utility maximisation. This research confirms that where a switch occurred for stochastic reasons, the previous main brand would remain in the consumer's consideration set with the same purchase probabilities for a brand of its size. On the other hand, where the brand switch occurred for reasons of expectation disconfirmation, the previous main brand was either removed entirely from the consumer's consideration set, or if it remained in the set, had a lower ranking than prior to the switch. While a brand switch that occurred for reasons of utility maximisation resulted in a majority of the previous main brands being removed from the consumer's consideration set, those that remained were ranked one place lower than the current main brand. Overall these results supported the research's general direction that the antecedents to a brand switch will affect the previous main brand's position in a consumer's post-switch purchase repertoire and consideration set. The research concludes, while the previous main brand may be gone, it is certainly not forgotten! These findings, while being exploratory and inductive, have important implications for marketers in both their recovery marketing campaigns and the need to implement programmes to retain recent acquisitions. Coupled with the findings from Sharp et al. (2002) this study shows that subscription markets, in terms of switching, behave in a similar manner to repertoire markets, allowing for stochastic models to be used to benchmark marketing activities.
Keywords: Mathematical models; Brand choice; Consumers' preferences; Marketing